The impact of concurrent HIV and type II diabetes on immune maturation, immune regulation and immune activation. Issue 7 (24th May 2019) - Tingstedt, Jeanette Linnea; Hove‐Skovsgaard, Malene; Gaardbo, Julie; Ullum, Henrik; Nielsen, Susanne Dam; Gelpi, Marco
Abstract : Chronic immune activation and inflammation are constant findings in people living with HIV (PLWH) and contribute to the risk of non‐AIDS‐related morbidities, including cardiovascular diseases (CVD). Type 2 diabetes (T2D) is also characterized by immune activation and inflammation. We aimed to investigate the impact of concurrent HIV infection and T2D on T‐cell subsets. The study included PLWH with T2D (HIV+T2D+, N = 25) and without T2D (HIV+T2D−, N = 25) and HIV‐negative controls with T2D (HIV−T2D+, N = 22) and without T2D (HIV−T2D−, N = 28). All PLWH in the study were receiving combination antiretroviral therapy. We examined T‐cell homeostasis by determining T‐cell subsets (immune maturation, immune regulation and immune activation) using flow cytometry. HIV+T2D− had lower proportion of Tc17 cells and higher proportion of apoptotic cells than HIV−T2D−. When comparing HIV+T2D+ and HIV+T2D− a lower proportion of CD4+ recent thymic emigrants (RTE) was found (p = 0.028). Furthermore, HIV+T2D+ had a higher proportion of non‐suppressive CD4+ Tregs compared to HIV+T2D− (p = 0.010). In conclusion, even in the setting of treated HIV infection, distinct immunological alterations are found. In PLWH with concomitant T2D, most alterations in T‐cell subsets were related to HIV and only few differences were found between PLWH with and without diabetes.